Gender diversity in firms - Ghazala Azmat; Anne Boring (Institute of Labor Economics (IZA), 2020)
This paper explores the recent efforts by the corporate world and public policy to increase the number of women in leadership positions in the workplace. We review and empirically evaluate the "business case" for gender equality, showing some evidence in favour of it. Despite the evidence and growing support, progress towards more diversity in leadership positions has been slow. We study the importance of supply-side constraints, as well as the main diversity policies (gender quotas, mentoring and network programs, diversity training to change firm culture, and family friendly policies) that have been implemented. We focus on the effectiveness of these policies, their shortcomings, as well as potential future steps that could help guide policy.
Keywords: J16; M14; 330; gender; firms; diversity policies